MENINGKATKAN MUTU PELAYANAN DI HOLLAND BAKERY TEGAL ROTAN DENGAN METODE IPA, KANO, DAN QFD - Marco Reinhart; Fuji Rahayu Wilujeng (JIEMS (Journal of Industrial Engineering and Management Systems), 2022)
Every year there is an increase that occurs so that the industry continues to compete to provide the best service, including the food industry. Service quality that is appropriate or even better than customer expectations will increase a customer's loyalty to the product or service provided. Holland Bakery itself already has more than 200 outlets throughout Indonesia spread in many cities. The quality of service provided by one of the Holland Bakery counters in Tegal Rotan can be seen by looking at the results of the answers from 30 customers on the initial questionnaire where 6 attributes with higher satisfaction and 11 attributes with higher dissatisfaction can be said that the quality of service provided is not good. . The research was conducted using four methods, namely servqual, IPA, Kano and QFD where servqual will be used to determine what attributes can satisfy customers through the use of five components and five gaps where it is found that there are 13 attributes that have negative gaps. After that, the IPA method will be used to find out the variables that need improvement by dividing them on a Cartesian diagram, the Kano method to determine the priority of attribute improvement according to the category, then the IPA and Kano methods will be integrated to get the "attributes that require improvement and will be brought into the QFD method. to improve service quality to match customer expectations and expectations by connecting the "voice of customer" into the overall service performed by the Tegal Rotan Holland Bakery counter where the technical response sequences that need to be carried out by companies to improve the quality of their services are obtained. This study shows that there are 13 attributes that have a negative gap, 10 attributes are in quadrant I and 3 attributes are in quadrant III, there are 13 attributes that are priorities for improvement, and technical responses that can be carried out on a priority basis to overcome the causes of problems or improve quality service.